Comparing the Impact of Titanium and Stainless Steel Retainers on Lower Incisor Stability, Periodontal Health, and Retainer Survival: A Preliminary Study - Melis Seki Yurdakul; Pamir Meriç (Turkish Journal of Orthodontics)
Objective: This study aims to compare the impact of titanium and stainless steel (SS) retainer wires on lower incisor stability and periodontal health. Methods: Fifty patients between the ages of 14.1 and 29.5 years were recruited for the study. The impact of 0.027x0.011-inch rectangular titanium dead-soft wire retainers was compared with that of 0.0215-inch six-stranded SS wire retainers. The retainers were bonded to the mandibular arch, and 3D models were evaluated after completion of the orthodontic treatment (T1), at the third month (T2), and at the sixth month (T3). Little’s irregularity index (LII), the intercanine width, the pocket depth, the plaque index, bleeding on probing, and retainer survival were analyzed. The generalized linear model method was used to compare scores on LII, the intercanine width, the pocket depth, and plaque index values. Cochran’s Q test was used to compare intragroup bleeding. Results: A significant increase was found in the irregularity index parameter according to time (p=0.004) but no statistically significant difference was found between groups in terms of the LII according to material and time (p=0.826). No significant difference was found in intercanine width parameters between the groups according to material and time (p=0.977). No statistically significant difference was found between the groups in terms of pocket depth and plaque index scores, according to material and time. No retainer failure was observed in either group. Conclusion: Both retainer wires offer successful results in terms of stability parameters and periodontal parameters after six months.